Revitalisasi Studi Implementasi Kebijakan Publik - Erwan Agus Purwanto (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2004)
In the recentyears, the implementation study is facing a difficult time since its emergence for several deracks ago. This challenging, as a matter of fact, is caused by of various factors. Among of these factors, only to mention several of them, are.-first, the emergence of new public administration (NPM) in the 1990s. Some scholars argued that NPM souk/ be utilized to remedy iheprohlems of implementation, which mainly is seen as the probkm of administrative and management. This development subsequently raises a critical question to the implementation stuch, whether this study should be continued or not. Second, the declining of the domination of the government as the sole agent which is responsible to implement the government polity as the consequence of the need for democratisation. The second development gives new pressure to the government to invite more active role of the civil society and private sectors, not only to implement the government polity, but also to set up policy agenda and to formulatepoliry. The involvement of various organisations in implementing government policies means that the administrative and management approaches to understand the problems of implementation are not relevant any longer. After discussing all of these problems, this article then argues that the implementation study should renew its approach if this study still wants to maintain its existence. To do so, this article suggests that the scholars who carryout research on this theme should understand the problems of implementation not only as administrative and management as such, but also as political problem as well. This means that the problems of implementation should be understood also as the dynamic of the relationships among the stakeholders who have interest to a certain kind of policy within the policy cycle.